2016
DOI: 10.21037/acs.2016.06.01
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management and outcomes of type A dissection—the Mayo Clinic experience

Abstract: Background: Type A aortic dissection (TAAD) is a complex cardiovascular disease that is associated with high perioperative morbidity and mortality. The most effective approach is still being debated-such as the best cannulation technique, and conservative versus extensive initial surgery. We reviewed our experience over the last 20 years and examined for variables that correlated with observed outcomes.Methods: All patients who underwent TAAD repair were reviewed. Chi-Square tests, Fisher Exact tests and Wilco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 31 publications
3
46
0
4
Order By: Relevance
“…It is clear that at least some of the impact on improving survival is related to these factors (18, 19). The overall operative mortality rate of 18.9% in this cohort, is consistent with the current literature (69, 1618, 2022). Mody et al demonstrated significant improvement in 30-day mortality for Medicare patients from 30.7% in 2000 to 21.4% in 2011, similar to an IRAD analysis where in-hospital mortality decreased from 25.0% in an era starting in 1996 to 18.4% currently (7, 8).…”
Section: Commentsupporting
confidence: 92%
See 2 more Smart Citations
“…It is clear that at least some of the impact on improving survival is related to these factors (18, 19). The overall operative mortality rate of 18.9% in this cohort, is consistent with the current literature (69, 1618, 2022). Mody et al demonstrated significant improvement in 30-day mortality for Medicare patients from 30.7% in 2000 to 21.4% in 2011, similar to an IRAD analysis where in-hospital mortality decreased from 25.0% in an era starting in 1996 to 18.4% currently (7, 8).…”
Section: Commentsupporting
confidence: 92%
“…The current literature is replete with contemporary outcomes from high volume hospitals or consortiums of aortic centers reporting improving outcomes with mortalities of 5–19% (35, 7, 9, 16, 17). These analyses suffer from the simple fact that their aortic teams, high volume aortic surgeons, and surgical and intensive care infrastructure may not be representative of the resources available to a majority of patients suffering TAAD.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…(Table 2). 10,12 In addition, when freedom from distal aortic reintervention was evaluated in these studies, extended or total arch aortic repair was not consistently shown to be better than the conventional limited repair group. 8,13,14 Initial Hybrid Aortic Repair…”
Section: Proximal Aortic Repair Onlymentioning
confidence: 91%
“…Aortic valve repair is necessary in over 50% of patients and is combined with proximal repair. 10 Aortic valve repair is beyond the scope of this review and will not be further discussed here. Early mortality rates for all proximal aortic repairs have continued to improve with reported rates from 4.4% to 9.9% at experienced sites and overall 1-year survival of more than 82%.…”
Section: Proximal Aortic Repair Onlymentioning
confidence: 99%